Confirmation of initial antiphospholipid antibody positivity depends on the antiphospholipid antibody profile. Issue 8 (14th August 2013) - Pengo, V.; Ruffatti, A.; Del Ross, T.; Tonello, M.; Cuffaro, S.; Hoxha, A.; Banzato, A.; Bison, E.; Denas, G.; Bracco, A.; Padayattil Jose, S.
Summary Background The revised classification criteria for the antiphospholipid syndrome state that antiphospholipid (aPL) antibodies (lupus anticoagulant [LAC] and/or anticardiolipin [aCL] and/or anti‐β2‐glycoprotein I [aβ2GPI] antibodies) should be detected on two or more occasions at least 12 weeks apart. Consequently, classification of patient risk and adequacy of treatment may be deferred by 3 months. Objectives In order to early classify patient risk, we evaluated whether aPL positivity confirmation is related to aPL antibody profiles. Patients and Methods Consecutive patients referred to our center who were initially positive in one or more tests exploring the presence of aPL were tested after 3 months. During a 4‐year period, 225 patients were initially positive in one or more tests, and 161 were available for confirmation after 3 months. Patients were classified as triple‐positive (n = 54: LAC+, aCL+, aβ2GPI+, same isotype), double‐positive (n = 50: LAC–, aCL+, aβ2GPI+, same isotype) and single‐positive (n = 53: LAC or aCL or aβ2GPI antibodies as the sole positive test). Results Among subjects with triple positivity at initial testing, 98% (53 of 54) had their aPL profile confirmed after 12 weeks. The double‐positive and single‐positive groups had data confirmed in 42 of 50 (84%) and 23 of 57 (40%) subjects, respectively. Conclusions Our results show that high‐risk subjects with triple‐positive aPL profiles are identified early, at the time of the initial screening tests.